Asuhan Keperawatan Pada An.K Dengan Gangguan Sistem Pernafasan: Bronkopneumonia di RSUD Dr. Soeselo Kabupaten Tegal - Hani Naviatul Latifah; Esti Nurjanah; Ahmad Zakiudin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Bronchopneumonia is an inflammatory condition of the lung parenchyma caused by microorganisms. Microorganisms enter the lungs through the respiratory tract into the bronchioles and alveoli and stimulate epithelial cells to produce mucus, causing accumulation of secretions in the alveoli (Utami et al., 2023). According to data from (WHO, 2022) In 2019, 740,180 people died from bronchopneumonia, which caused 14% of deaths in children under 5 years. The number of bronchopneumonia cases in children in developing countries is 82% higher compared to 0.5% cases in developed countries (Syahrinisya et al., 2024). The purpose of this writing is for the author to be able to create and apply nursing care to Patient. K with respiratory system disorders: bronchopneumonia at dr. Soeselo, Regional Hospital, Tegal Regency. The method used is that the nurse will collect basic data in the form of assessment from interviews, physical examination, observation, laboratory examination results and diagnosis. From the case review, it was found that the main complaint was that the client's mother stated that her child was coughing up phlegm. There were three diagnoses found, namely ineffective airway clearance, anxiety, knowledge deficit. Interventions are structured based on the theory of SDKI, SLKI and SIKI as well as on the client's condition and can be implemented.